High-performance ceramic water permeable brick and preparation method thereof

The preparation of multi-layered ceramic permeable bricks through 3D printing technology solves the problems of insufficient strength and poor water permeability of existing permeable bricks, and realizes high-strength, high water permeability and organic degradation functions, extends service life and reduces maintenance costs.

CN119615692APending Publication Date: 2025-03-14WUHAN METALLURGY ARCHITECTURE RES YUAN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411809198.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing permeable bricks have problems such as poor permeability, insufficient strength, easy to break, and short service life. They cannot effectively solve the problem of urban waterlogging and are easily damaged during use, which increases the cost of municipal construction and causes waste of resources.

Method used

The bottom large-particle solid waste structure, the middle-layer high-strength structural layer, the bonding layer and the surface porous ceramic layer are prepared in sequence from bottom to top. Through special material ratios and structural design, ceramic permeable bricks with high strength, high permeability and organic degradation functions are formed.

Benefits of technology

It realizes the high strength, high water permeability and organic degradation functions of ceramic permeable bricks, extends the service life, reduces maintenance costs, and effectively solves the problem of urban waterlogging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615692A_ABST
    Figure CN119615692A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance ceramic water permeable brick and a preparation method thereof. The high-performance ceramic water permeable brick sequentially comprises a bottom-layer large-particle solid waste structure, a middle-layer high-strength structure layer, a bonding layer and a surface-layer porous ceramic layer from bottom to top, the bottom-layer large-particle solid waste structure, the middle-layer high-strength structure layer, the bonding layer and the surface-layer porous ceramic layer are sequentially prepared from bottom to top through a 3D printing technology; a plurality of gaps are arranged in the middle-layer high-strength structure layer, and each gap forms a venturi structure in the radial direction; the two ends of an opening of the venturi structure are connected with the bottom-layer large-particle solid waste structure and the bonding layer correspondingly. The high-performance ceramic water permeable brick provided by the invention has high strength, high water permeability and an organic matter degradation function, and the surface is not easy to block.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic permeable bricks, and in particular to high-performance ceramic permeable bricks and a preparation method thereof. Background Art

[0002] Under the background of accelerating urbanization, permeable bricks are indispensable environmentally friendly building materials in urban construction. Their performance and quality have an important impact on the urban environment, ecological balance and the quality of life of citizens. At present, there are many types of permeable bricks on the market, but there are some common problems.

[0003] In the prior art, ordinary permeable bricks often have problems such as poor permeability, insufficient strength, easy breakage, and short service life. These permeable bricks often rely only on the small water absorption capacity of the brick body itself or the gaps between bricks for water permeability. The permeability effect is limited, and the surface of the permeable bricks is easily blocked, which cannot effectively solve the problem of urban waterlogging. At the same time, due to insufficient strength, these permeable bricks are easily damaged during use and need to be replaced frequently, which not only increases the cost of municipal construction, but also causes a waste of resources. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide high-performance ceramic permeable bricks and a preparation method thereof in view of the deficiencies in the prior art. The high-performance ceramic permeable bricks provided by the present invention have high strength, high permeability and organic degradation function, and the surface is not easily clogged.

[0005] The technical solution adopted by the present invention to solve the above-mentioned problems is:

[0006] A high-performance ceramic water-permeable brick, the high-performance ceramic water-permeable brick comprising, from bottom to top, a bottom layer of large-particle solid waste structure (1), a middle layer of high-strength structural layer (2), a bonding layer (3) and a surface porous ceramic layer (4); the bottom layer of large-particle solid waste structure (1), the middle layer of high-strength structural layer (2), the bonding layer (3) and the surface porous ceramic layer (4) are prepared from bottom to top by 3D printing technology; a plurality of voids are arranged in the middle layer of high-strength structural layer (2), and each of the voids forms a venturi structure in the radial direction; and the two ends of the opening of the venturi structure are respectively connected to the bottom layer of large-particle solid waste structure (1) and the bonding layer (3).

[0007] According to the above scheme, the bottom layer of large solid waste particles (1) comprises the following raw materials in parts by weight: 50-60 parts of solid waste materials, 25-35 parts of ceramic raw materials, 1-3 parts of plasticizers, and 1-3 parts of dispersants; the bottom layer of large solid waste particles (1) has a thickness of 20-35 mm;

[0008] The middle-layer high-strength structural layer (2) comprises the following raw materials in parts by weight: 60-75 parts of ceramic raw materials, 20-25 parts of solid waste materials, 3-5 parts of plasticizers, and 2-3 parts of dispersants; the middle-layer high-strength structural layer (2) has a thickness of 35-45 mm;

[0009] The bonding layer (3) comprises the following raw materials in parts by mass: 3 to 5 parts of high-strength fiber and 5 to 10 parts of ceramic raw materials; the bonding layer (3) has a thickness of 2 to 5 mm;

[0010] The surface porous ceramic layer (4) comprises the following raw materials in parts by mass: 15 to 23 parts of solid waste materials, 60 to 70 parts of ceramic raw materials, 3 to 5 parts of plasticizers, 2 to 3 parts of dispersants, 5 to 7 parts of pore-forming agents, 6 to 8 parts of bioactive substances, and 2 to 15 parts of catalysts; the thickness of the surface porous ceramic layer (4) is 5 to 18 mm.

[0011] According to the above scheme, the solid waste material is waste ceramic fragments or glass fragments; the solid waste material is used in different parts of the high-performance ceramic permeable brick according to the particle size, wherein the particle size of the solid waste material in the bottom large-particle solid waste structure (1) is 3-5 mm, the particle size of the solid waste material in the middle high-strength structural layer (2) is 3-6 mm, and the particle size of the solid waste material in the surface porous ceramic layer (4) is 0.5-2 mm. The reasons for selecting waste ceramic fragments or glass fragments as aggregates are: (1) Broken ceramic pieces and glass pieces have high strength, and as aggregates, they can better improve the overall strength; (2) Due to the similar chemical composition to the ceramic raw materials, they have high bonding strength with the ceramic raw materials and can be better bonded together; (3) The large-scale application of waste materials can effectively save costs.

[0012] According to the above scheme, the ceramic raw material is a mixture of aluminum oxide and silicon oxide; the mass ratio of silicon oxide to aluminum oxide is 3:2 to 2:1; the aluminum oxide is α-Al2O3 with a particle size of 0.5 to 10 microns; the silicon oxide is silicon dioxide powder with a particle size of 1 to 10 microns.

[0013] According to the above scheme, the plasticizer is polyethylene glycol or polyvinyl alcohol. The plasticizer is used to improve the plasticity and sintering performance of the raw material, improve the 3D printing performance, and ensure that the shape is not easy to collapse after being extruded by the 3D printing nozzle.

[0014] According to the above scheme, the dispersant is sodium polyacrylate or sodium silicate. The dispersant is used to prevent the raw materials from agglomerating during the mixing process. By controlling the amount of the dispersant, the drying time can be controlled to avoid the product collapsing due to gravity due to excessive drying time.

[0015] According to the above scheme, the high-strength fiber is one of zirconium oxide fiber, carbon fiber, ultra-high molecular weight polyethylene fiber, and polybenzimidazole fiber. The high-strength fiber is used to enhance the strength and toughness of the brick body, and can also filter particles in the water to ensure that organic matter is effectively decomposed on the surface and does not fall to the lower layer to block the channel.

[0016] According to the above scheme, the pore-forming agent is a combustible substance, including wood fiber, carbon powder, and coal ash. The pore-forming agent is used to form pores during the sintering process to improve water permeability.

[0017] According to the above scheme, the catalyst is nano titanium dioxide; the biologically active substance is activated carbon or biochar.

[0018] Due to the high-temperature stability of nano-titanium dioxide, its photocatalytic degradation function of organic matter can be maintained even during high-temperature sintering; in addition, the addition of activated carbon and biochar not only provides a dispersion medium for nano-titanium dioxide, but also ensures that the function of biologically active substances is not affected during the sintering process due to its heat resistance.

[0019] The present invention also provides a method for preparing the high-performance ceramic permeable brick, comprising the following steps:

[0020] (1) preparing raw materials of the bottom large-particle solid waste structure (1), the middle high-strength structural layer (2), the bonding layer (3) and the surface porous ceramic layer (4), and performing pretreatment;

[0021] (2) mixing the raw materials of each layer uniformly to form a slurry;

[0022] (3) using 3D printing technology according to preset model data, using the slurry obtained in step (2) to print the bottom large particle solid waste structure (1), the middle high strength structure layer (2), the bonding layer (3) and the surface porous ceramic layer (4) layer by layer from bottom to top to obtain a ceramic permeable brick;

[0023] (4) Drying and sintering the ceramic permeable bricks obtained in step (3) to obtain the high-performance ceramic permeable bricks.

[0024] According to the above scheme, the pretreatment in step (1) includes premixing and drying; the premixing is to stir and mix the catalyst and the biologically active substance in advance; for raw materials with a humidity of 20%, drying treatment is required, the drying temperature is 600-750°C, and the drying time is 3-5h;

[0025] According to the above scheme, the drying conditions in step (4) are: temperature of 20°C to 30°C, humidity of 75%Rh to 90%Rh; the specific method of sintering is: (1) in the pre-firing stage, the dried ceramic permeable bricks are heated to a preset temperature of 800 to 1000°C, wherein the heating rate is 100 to 150°C / min; (2) in the sintering stage, the temperature is continuously increased at a heating rate of 100 to 150°C / min to a sintering temperature of 1000 to 1050°C and kept at this temperature for 3 to 8 hours; (3) in the cooling stage, after sintering, the cooling rate is controlled at 45 to 60°C / min to cool to room temperature.

[0026] In the present invention, through a special preparation process and structural design, the high strength, high water permeability and organic degradation function of ceramic permeable bricks are achieved. Specifically, the present invention uses solid waste materials such as ceramic waste as raw materials, prepares the raw materials of ceramic permeable bricks by a sol-gel method, and uses 3D printing technology to prepare ceramic permeable bricks with complex spatial structures. Its strength is higher than that of ordinary permeable bricks. At the same time, the ceramic permeable bricks adopt a multi-layer structure design, and each layer of material ratio and function are clear to ensure the overall excellent water permeability. The bottom large-particle solid waste structure is cross-linked with each other through ceramic as an adhesive material to provide basic support; the middle high-strength structural layer uses high-strength and high-density ceramics to form a Venturi structure to ensure overall strength; the bonding layer (filter layer) is provided with a zirconium oxide fiber layer as an interface layer to stably connect the upper and lower structures, and filter impurities to ensure the durability of the permeable bricks; the surface porous ceramic layer absorbs water and degrades organic matter through capillary action to achieve efficient water permeability.

[0027] In the present invention, the surface porous ceramic layer combines the photocatalytic degradation function of nano-titanium dioxide with the efficient adsorption characteristics of activated carbon and biochar, and can degrade organic matter to avoid clogging. The present invention achieves uniform dispersion and fixation of nano-titanium dioxide by adding nano-titanium dioxide to the surface of the permeable brick and utilizing the nanoscale pore structure of activated carbon and biochar. This structural design not only ensures the high dispersibility of nano-titanium dioxide and avoids its agglomeration problem in application, but also utilizes the biological activity of activated carbon and biochar to promote the degradation efficiency of organic matter, so that the permeable brick can prevent the surface capillary water absorption design from decreasing due to organic matter clogging. The design of the surface porous ceramic layer also draws on the capillary water absorption principle. By adjusting the pore structure and material ratio, the surface of the permeable brick has a stronger water absorption capacity. At the same time, the activated carbon porous material can also effectively increase the specific surface area of ​​the permeable brick surface, improve the water absorption effect, and fix more water, which helps the permeable brick to play the role of water storage, and helps to quickly absorb water at the beginning of rainfall and reduce the pressure of the drainage system. The middle high-strength structural layer adopts the Venturi design, which uses the principle of fluid dynamics to accelerate the flow of water and improve the water permeability efficiency. It can still maintain good water permeability when dealing with large-volume rainwater. After a period of use, the permeable bricks can be cleaned from the surface with a high-pressure water gun or a high-pressure air gun. Due to the design of the Venturi structure, when the permeable bricks are cleaned to restore their water permeability, the inside of the permeable bricks can be more effectively flushed, improving the re-cleaning effect, which helps to extend the service life of the permeable bricks and reduce maintenance costs.

[0028] In the 3D printing process of the present invention, by accurately adjusting the ratio of plasticizer and dispersant, the viscosity of the mixture is controlled within the required range suitable for the extrusion of 3D printing consumables. Specifically, the viscosity of the mixture is adjusted to 30,000 to 35,000 mPa·s by accurately adjusting the ratio of plasticizer and dispersant. This range can ensure that the mixture is smoothly extruded in the 3D printing nozzle, and the shape is not easy to collapse and deform after printing. In order to further enhance the extrusion performance of the mixture, the present invention adopts a special mixing process, which includes premixing and high-speed stirring of the raw materials to ensure that the plasticizer and dispersant are evenly dispersed in the mixture. In addition, by controlling the drying time and temperature, the viscosity and stability of the mixture can be further optimized, thereby improving the yield and quality of 3D printing. In terms of pore formation, the present invention forms uniformly distributed pores during the sintering process by adding an appropriate amount of pore-forming agent, such as wood fiber, carbon powder, etc. The amount of pore-forming agent added is accurately calculated according to the required porosity and pore size to ensure that the permeable brick maintains the integrity and stability of the structure while meeting the permeability.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention provides a high-strength porous ceramic permeable brick with organic degradation function prepared by using 3D printing technology and solid waste materials. The permeable brick uses layered 3D printing technology and combines raw materials with different proportions to form a bottom layer of large-particle solid waste structure, a middle layer of high-strength structural layer, a bonding layer (filter layer) and a surface porous ceramic layer, so that the permeable brick achieves high strength, high permeability and organic degradation function. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic structural diagram of a high-performance ceramic permeable brick according to an embodiment of the present invention.

[0032] Figure 2 This is a venturi structure diagram and specific dimensions of the middle high-strength structural layer of the high-performance ceramic permeable brick in an embodiment of the present invention. DETAILED DESCRIPTION

[0033] The technical solution of the present invention will be fully and clearly described below in conjunction with specific embodiments, but the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0034] In a specific embodiment, the solid waste material used is discarded ceramic fragments or glass fragments; the ceramic raw material is a mixture of aluminum oxide and silicon oxide, wherein the mass ratio of silicon oxide to aluminum oxide is 3:2 to 2:1; the aluminum oxide is α-Al2O3, and the particle size is 0.5 to 10 microns; the silicon oxide is silicon dioxide powder, and the particle size is 1 to 10 microns; the plasticizer is polyethylene glycol or polyvinyl alcohol; the dispersant is sodium polyacrylate or sodium silicate; the high-strength fiber is one of zirconium oxide fiber, carbon fiber, ultra-high molecular weight polyethylene fiber, and polybenzimidazole fiber; the pore-forming agent is a combustible substance, including wood fiber, carbon powder, and coal ash; the catalyst is nano titanium dioxide; and the biologically active substance is activated carbon or biochar.

[0035] The present invention provides a high-performance ceramic water-permeable brick, such as Figure 1 As shown, the high-performance ceramic permeable brick includes, from bottom to top, a bottom layer of large-particle solid waste structure 1, a middle layer of high-strength structural layer 2, a bonding layer 3 and a surface porous ceramic layer 4; the bottom layer of large-particle solid waste structure 1, the middle layer of high-strength structural layer 2, the bonding layer 3 and the surface porous ceramic layer 4 are prepared from bottom to top by 3D printing technology; a plurality of voids are arranged in the middle layer of high-strength structural layer 2, and each void forms a venturi structure in the radial direction; the two ends of the opening of the venturi structure are respectively connected to the bottom layer of large-particle solid waste structure 1 and the bonding layer 3.

[0036] The above-mentioned method for preparing a high-performance ceramic permeable brick comprises the following steps:

[0037] (1) preparing raw materials for the bottom large-particle solid waste structure 1, the middle high-strength structural layer 2, the bonding layer 3 and the surface porous ceramic layer 4, and performing pretreatment;

[0038] (2) mixing the raw materials of each layer uniformly to form a slurry;

[0039] (3) using 3D printing technology according to preset model data, using the slurry obtained in step (2) to print the bottom large particle solid waste structure 1, the middle high strength structure layer 2, the bonding layer 3 and the surface porous ceramic layer 4 layer by layer from bottom to top to obtain a ceramic permeable brick;

[0040] (4) Drying and sintering the ceramic permeable bricks obtained in step (3) to obtain high-performance ceramic permeable bricks.

[0041] Specifically, the pretreatment in step (1) includes premixing and drying; wherein the premixing is to stir and mix the catalyst and the biologically active substance in advance; for raw materials with a humidity (water content) of 20%, drying treatment is required, the drying temperature is 600-750° C., and the drying time is 3-5 hours;

[0042] The drying conditions in step (4) are: temperature of 20°C to 30°C, humidity of 75%Rh to 90%Rh; the specific method of sintering is: (1) in the pre-firing stage, the dried ceramic permeable bricks are heated to a preset temperature of 800 to 1000°C, wherein the heating rate is 100 to 150°C / min; (2) in the sintering stage, the temperature is continuously increased at a heating rate of 100 to 150°C / min to a sintering temperature of 1000 to 1050°C and kept at this temperature for 3 to 8 hours; (3) in the cooling stage, after sintering, the temperature is cooled to room temperature at a cooling rate of 45 to 60°C / min.

[0043] Example 1

[0044] A high-performance ceramic permeable brick, wherein a bottom layer of large-particle solid waste structure 1 comprises the following raw materials in mass fractions: 55 parts of solid waste material discarded ceramic fragments (water content 10%, particle size 3-5 mm), 18 parts of silicon dioxide powder, 12 parts of aluminum oxide, 2 parts of polyethylene glycol, and 2 parts of sodium polyacrylate; a middle layer of high-strength structural layer 2 comprises the following raw materials in mass fractions: 22 parts of aluminum oxide, 43 parts of silicon dioxide powder, 22 parts of discarded ceramic fragments (particle size 3-6 mm), 4 parts of polyvinyl alcohol, and 2.5 parts of sodium polyacrylate; a bonding layer 3 comprises the following raw materials in mass fractions: 4 parts of zirconium oxide fiber, 3 parts of aluminum oxide, and 5 parts of silicon dioxide powder; a surface porous ceramic layer 4 comprises the following raw materials in mass fractions: 18 parts of discarded ceramic fragments (particle size 0.5-2 mm), 22 parts of aluminum oxide, 43 parts of silicon dioxide powder, 4 parts of polyvinyl alcohol, 2.5 parts of sodium polyacrylate, 6 parts of wood fiber, 10 parts of nano titanium dioxide, and 6 parts of activated carbon.

[0045] The preparation method of the above-mentioned high-performance ceramic permeable brick is:

[0046] (1) preparing raw materials of a bottom large-particle solid waste structure 1, a middle high-strength structural layer 2, a bonding layer 3, and a surface porous ceramic layer 4, and performing pretreatment; the pretreatment includes stirring and mixing the activated carbon and nano-titanium dioxide in advance;

[0047] (2) mixing the raw materials of each layer uniformly to form a slurry;

[0048] (3) Using 3D printing technology according to preset model data, the slurry obtained in step (2) is used to print the bottom large particle solid waste structure 1 (thickness 30 mm), the middle high strength structure layer 2 (thickness 40 mm), the bonding layer 3 (thickness 3 mm) and the surface porous ceramic layer 4 (thickness 6 mm) layer by layer from bottom to top to obtain a ceramic permeable brick;

[0049] (4) Drying and sintering the ceramic permeable bricks obtained in step (3) to obtain high-performance ceramic permeable bricks; wherein the drying conditions are: temperature of 23°C and humidity of 85%Rh; the specific sintering method is: (1) pre-firing stage, heating the dried ceramic permeable bricks to a preset temperature of 920°C, wherein the heating rate is 125°C / min; (2) sintering stage, continuing to heat at a heating rate of 125°C / min to a sintering temperature of 1000°C and keeping the temperature for 6.5 hours; (3) cooling stage, after sintering, controlling the cooling rate to cool to room temperature at 50°C / min.

[0050] Example 2

[0051] A high-performance ceramic permeable brick, wherein a bottom layer of large-particle solid waste structure 1 comprises the following raw materials in mass fractions: 52 parts of waste ceramic fragments (water content 26%, particle size 3-5 mm), 17 parts of silicon dioxide powder, 11 parts of aluminum oxide, 1.5 parts of polyethylene glycol, and 1.5 parts of sodium polyacrylate; a middle layer of high-strength structural layer 2 comprises the following raw materials in mass fractions: 24 parts of aluminum oxide, 46 parts of silicon dioxide powder, 20 parts of waste ceramic fragments (particle size 3-6 mm), 3.5 parts of polyethylene glycol, and 2 parts of sodium polyacrylate; a bonding layer 3 comprises the following raw materials in mass fractions: 3.5 parts of zirconium oxide fiber, 2 parts of aluminum oxide, and 4 parts of silicon dioxide powder; a surface porous ceramic layer 4 comprises the following raw materials in mass fractions: 20 parts of waste ceramic fragments (particle size 0.5-2 mm), 23 parts of aluminum oxide, 46 parts of silicon dioxide powder, 3.5 parts of polyvinyl alcohol, 2 parts of sodium polyacrylate, 5.5 parts of wood fiber, 6 parts of nano titanium dioxide, and 6 parts of activated carbon.

[0052] The preparation method of the above-mentioned high-performance ceramic permeable brick is:

[0053] (1) First, the solid waste material (abandoned ceramic fragments) is dried (temperature 700° C., time 3 hours), and the raw materials of the bottom large-particle solid waste structure 1, the middle high-strength structural layer 2, the bonding layer 3 and the surface porous ceramic layer 4 are prepared and pre-treated; the pre-treatment includes stirring and mixing the activated carbon and nano-titanium dioxide in advance;

[0054] (2) mixing the raw materials of each layer uniformly to form a slurry;

[0055] (3) Using 3D printing technology according to preset model data, the slurry obtained in step (2) is used to print the bottom large particle solid waste structure 1 (thickness 30 mm), the middle high strength structure layer 2 (thickness 40 mm), the bonding layer 3 (thickness 3 mm) and the surface porous ceramic layer 4 (thickness 8 mm) layer by layer from bottom to top to obtain a ceramic permeable brick;

[0056] (4) Drying and sintering the ceramic permeable bricks obtained in step (3) to obtain high-performance ceramic permeable bricks; wherein the drying conditions are: temperature of 20°C and humidity of 75%Rh; the specific sintering method is: (1) pre-firing stage, heating the dried ceramic permeable bricks to a preset temperature of 800°C, wherein the heating rate is 100°C / min; (2) sintering stage, continuing to heat at a heating rate of 100°C / min to a sintering temperature of 1050°C and keeping the temperature for 6 hours; (3) cooling stage, after sintering, controlling the cooling rate to cool to room temperature at 50°C / min.

[0057] Example 3

[0058] A high-performance ceramic permeable brick, wherein the bottom large-particle solid waste structure 1 includes the following raw materials in mass parts: 58 parts of waste ceramic fragments (water content 26%, particle size 3-5 mm), 17 parts of silicon dioxide powder, 10 parts of aluminum oxide, 2.5 parts of polyethylene glycol, and 2.5 parts of sodium polyacrylate; the middle high-strength structural layer 2 includes the following raw materials in mass parts: 48 parts of silicon dioxide powder, 24 parts of aluminum oxide, 24 parts of waste ceramic fragments (particle size 3-6 mm), polyethylene glycol, and 2.5 parts of sodium polyacrylate. The composition comprises 4.5 parts of glycol and 2.5 parts of sodium polyacrylate; the bonding layer 3 comprises the following raw materials in parts by mass: 5 parts of zirconium oxide fiber, 4 parts of silica powder and 2 parts of alumina; the surface porous ceramic layer 4 comprises the following raw materials in parts by mass: 22 parts of waste ceramic fragments (with a particle size of 0.5 to 2 mm), 42 parts of silica powder, 25 parts of alumina, 4.5 parts of polyethylene glycol, 2.5 parts of sodium polyacrylate, 6.5 parts of wood fiber, 4 parts of nano titanium dioxide and 7 parts of activated carbon.

[0059] The preparation method of the above-mentioned high-performance ceramic permeable brick is:

[0060] (1) First, the solid waste material (abandoned ceramic fragments) is dried (temperature 700° C., time 3 hours), and the raw materials of the bottom large-particle solid waste structure 1, the middle high-strength structural layer 2, the bonding layer 3 and the surface porous ceramic layer 4 are prepared and pre-treated; the pre-treatment includes stirring and mixing the activated carbon and nano-titanium dioxide in advance;

[0061] (2) mixing the raw materials of each layer uniformly to form a slurry;

[0062] (3) Using 3D printing technology according to preset model data, the slurry obtained in step (2) is used to print the bottom large particle solid waste structure 1 (thickness 35 mm), the middle high strength structure layer 2 (thickness 40 mm), the bonding layer 3 (thickness 3 mm) and the surface porous ceramic layer 4 (thickness 10 mm) layer by layer from bottom to top to obtain a ceramic permeable brick;

[0063] (4) Drying and sintering the ceramic permeable bricks obtained in step (3) to obtain high-performance ceramic permeable bricks; wherein the drying conditions are: temperature of 23°C and humidity of 80%Rh; the specific sintering method is: (1) pre-firing stage, heating the dried ceramic permeable bricks to a preset temperature of 850°C, wherein the heating rate is 110°C / min; (2) sintering stage, continuing to heat at a heating rate of 110°C / min to a sintering temperature of 1010°C and keeping the temperature for 4.5 hours; (3) cooling stage, after sintering, controlling the cooling rate to cool to room temperature at 50°C / min.

[0064] Comparative Example 1

[0065] This comparative example is basically the same as Example 1, except that: no venturi structure is formed in the middle high-strength structural layer 2, and the original venturi structure is partially replaced by the bottom large-particle solid waste structure 1.

[0066] Comparative Example 2

[0067] This comparative example is basically the same as Example 1, except that: nano titanium dioxide and activated carbon are not used in the surface porous ceramic layer 4.

[0068] Comparative Example 3

[0069] This comparative example is basically the same as Example 1, except that: no pore-forming agent wood fiber is used in the surface porous ceramic layer 4 .

[0070] The venturi structure and its specific dimensions formed in the middle high-strength structural layer 2 of the high-performance ceramic permeable brick in Examples 1 to 3 are as follows: Figure 2 ( Figure 2The Venturi structure is in a vertical direction, the bottom is connected to the bottom large particle solid waste structure 1, and the top is connected to the bonding layer 3), as shown in Examples 2 and 3, the Venturi structure is optimized; the compressive strength, water permeability and organic degradation rate of the high-performance ceramic permeable bricks prepared in Examples 1 to 3 and the ceramic permeable bricks prepared in Comparative Examples 1 to 3 were tested, and the test results are shown in the following table:

[0071] Table 1

[0072]

[0073] From Table 1 and Figure 2 It can be seen that the optimized venturi structure in Example 2 can improve the water permeability while ensuring the strength. Example 3 shows that although the further optimized venturi structure can improve the water permeability, it will also affect the strength. In addition, Table 1 also shows that the organic degradation ability of high-performance ceramic permeable bricks can be improved with the increase of nano-titanium dioxide dosage.

[0074] In summary, the present invention provides a high-performance ceramic permeable brick, which has high strength, high permeability and organic degradation function, and the surface is not easy to be blocked.

[0075] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A high performance ceramic permeable brick, characterized in that: The high-performance ceramic permeable brick comprises, from bottom to top, a bottom layer of large-particle solid waste structure (1), a middle layer of high-strength structural layer (2), a bonding layer (3) and a surface porous ceramic layer (4); the bottom layer of large-particle solid waste structure (1), the middle layer of high-strength structural layer (2), the bonding layer (3) and the surface porous ceramic layer (4) are prepared from bottom to top by 3D printing technology; a plurality of voids are arranged in the middle layer of high-strength structural layer (2), and each of the voids forms a venturi structure in the radial direction; and the two ends of the opening of the venturi structure are respectively connected to the bottom layer of large-particle solid waste structure (1) and the bonding layer (3).

2. The high performance ceramic permeable brick according to claim 1, characterized in that: The bottom layer of large solid waste particles (1) comprises the following raw materials in parts by weight: 50-60 parts of solid waste materials, 25-35 parts of ceramic raw materials, 1-3 parts of plasticizers, and 1-3 parts of dispersants; the bottom layer of large solid waste particles (1) has a thickness of 20-35 mm; The middle-layer high-strength structural layer (2) comprises the following raw materials in parts by weight: 60-75 parts of ceramic raw materials, 20-25 parts of solid waste materials, 3-5 parts of plasticizers, and 2-3 parts of dispersants; the middle-layer high-strength structural layer (2) has a thickness of 35-45 mm; The bonding layer (3) comprises the following raw materials in parts by mass: 3 to 5 parts of high-strength fiber and 5 to 10 parts of ceramic raw materials; the bonding layer (3) has a thickness of 2 to 5 mm; The surface porous ceramic layer (4) comprises the following raw materials in parts by mass: 15 to 23 parts of solid waste materials, 60 to 70 parts of ceramic raw materials, 3 to 5 parts of plasticizers, 2 to 3 parts of dispersants, 5 to 7 parts of pore-forming agents, 6 to 8 parts of bioactive substances, and 2 to 15 parts of catalysts; the thickness of the surface porous ceramic layer (4) is 5 to 18 mm.

3. The high performance ceramic permeable brick according to claim 2, characterized in that: The solid waste material is discarded ceramic fragments or glass fragments; wherein the particle size of the solid waste material in the bottom large-particle solid waste structure (1) is 3 to 5 mm, the particle size of the solid waste material in the middle high-strength structural layer (2) is 3 to 6 mm, and the particle size of the solid waste material in the surface porous ceramic layer (4) is 0.5 to 2 mm.

4. The high performance ceramic permeable brick according to claim 2, characterized in that: The ceramic raw material is a mixture of aluminum oxide and silicon oxide; the mass ratio of silicon oxide to aluminum oxide is 3:2 to 2:1; the aluminum oxide is α-Al2O3 with a particle size of 0.5 to 10 microns; the silicon oxide is silicon dioxide powder with a particle size of 1 to 10 microns.

5. The high performance ceramic permeable brick according to claim 2, characterized in that: The plasticizer is polyethylene glycol or polyvinyl alcohol.

6. The high performance ceramic permeable brick according to claim 2, characterized in that: The dispersant is sodium polyacrylate or sodium silicate.

7. The high performance ceramic permeable brick according to claim 2, characterized in that: The high-strength fiber is one of zirconium oxide fiber, carbon fiber, ultra-high molecular weight polyethylene fiber and polybenzimidazole fiber; the pore-forming agent is a combustible substance, including wood fiber, carbon powder and coal ash.

8. The high performance ceramic permeable brick according to claim 2, characterized in that: The catalyst is nano titanium dioxide; the biologically active substance is activated carbon or biochar.

9. The method for preparing the high performance ceramic permeable brick according to claim 2, characterized in that: The steps include: (1) preparing raw materials of the bottom large-particle solid waste structure (1), the middle high-strength structural layer (2), the bonding layer (3) and the surface porous ceramic layer (4), and performing pretreatment; (2) mixing the raw materials of each layer uniformly to form a slurry; (3) using 3D printing technology according to preset model data, using the slurry obtained in step (2) to print the bottom large particle solid waste structure (1), the middle high strength structure layer (2), the bonding layer (3) and the surface porous ceramic layer (4) layer by layer from bottom to top to obtain a ceramic permeable brick; (4) Drying and sintering the ceramic permeable bricks obtained in step (3) to obtain the high-performance ceramic permeable bricks.

10. The method for preparing the high performance ceramic permeable brick according to claim 9, characterized in that: The pretreatment in step (1) includes premixing and drying; the premixing is to stir and mix the catalyst and the biologically active substance in advance; the drying temperature is 600-750° C., and the drying time is 3-5 hours; The drying conditions in step (4) are: temperature of 20°C to 30°C, humidity of 75%Rh to 90%Rh; the specific method of sintering is: (1) in the pre-firing stage, the dried ceramic permeable bricks are heated to a preset temperature of 800 to 1000°C, wherein the heating rate is 100 to 150°C / min; (2) in the sintering stage, the temperature is continuously increased at a heating rate of 100 to 150°C / min to a sintering temperature of 1000 to 1050°C and kept at this temperature for 3 to 8 hours; (3) in the cooling stage, after sintering, the temperature is cooled to room temperature at a cooling rate of 45 to 60°C / min.